Francis Bacon. Dipingere le forze - Cantone, Damiano (Scenari, 2021)
This essay examines the Deleuzian reflection on Francis Bacon’s painting, framing it within the more general reflection of the French thinker on the Aesthetics. The theme of “force” – of painting the forces – provides the trait du union between the chapters of this work. Through the analysis of some meaningful Bacon’s paintings, we analyze traditional concepts of Aesthetic Philosophy, such as space, representation, figure, to read them in the light of a theory of intensive space. The Deleuzian hypothesis is that in order to overcoming the figurative logic, we need to access to another discursive level – that of the logic of sensation – which is governed by a different relationship between spectator and image. The figurative is substituted for the figurative, the visual the haptic, the witness the spectator. The breaking of the representative paradigm, and the abolishing the distance between the user and the work it establishes, opens up the possibility of “making visible invisible forces”.